Sulle tracce di Aria Nova: il canto ara petrejancara nella Calabria centrale (De Musica, 2024)
The canto ara petrejancara is a vocal tradition that originated in the mountains of central Tyrrhenian Calabria. These two- or three-part polyvocal songs are sung at a free, non-measured slow tempo, typically accompanied by the diatonic accordion. Songs in this style have been documented in several audio recordings, including those by Alan Lomax and Walter Hennig, who published the relatively well-known track Aria Nova in 1954. Despite being still practised in the region, little information is available on the canto ara petrejancara to date, making it an understudied phenomenon in Italian ethnomusicology. This paper aims to fill this gap by discussing both historical and contemporary manifestations of the ara petrejancara style through music analysis and ethnographic data. This article starts with an analysis of the little information provided by Hennig about Aria Nova to position this recording in the broader context of central Calabria music. After providing an analysis of Aria Nova, the article reviews the historical audio recordings of songs in this style documented from the 1950s onward and discusses their stylistic features. It then analyses a recent recording that depicts the current state of the canto ara petrejancara. This recording is compared with the historical recordings in light of the rich ethnographic data gained through participant observation and direct involvement in the local community of musicians.